MRNA and miRNA expression profiling of follicular variant of papillary thyroid carcinoma with and without distant metastases. (5th January 2019) - Condello, Vincenzo; Torregrossa, Liborio; Sartori, Chiara; Denaro, Maria; Poma, Anello Marcello; Piaggi, Paolo; Valerio, Laura; Materazzi, Gabriele; Elisei, Rossella; Vitti, Paolo; Basolo, Fulvio
Abstract: Follicular Variant of Papillary Thyroid Carcinoma (FVPTC) is usually associated with a good outcome. Nevertheless, in rare cases, it develops distant metastases (1–9%). Our goal was to investigate whether mRNA and miRNA expression profiles may help distinguish between metastatic versus non-metastatic FVPTCs. Twenty-four primary FVPTCs, 12 metastatic and 12 non-metastatic, with similar clinicopathological features were selected and analyzed by nanoString nCounter technology using two distinct panels for expression analysis of 740 mRNA and 798 miRNAs. Data analysis was performed using the nanoString nSolver 3.0 software. Forty-seven mRNA and 35 miRNAs were differentially expressed between the two groups. Using these mRNA and miRNAs, metastatic and non-metastatic FVPTCs were clearly divided into two distinct clusters. Our results indicate that FVPTCs with metastatic abilities have different expression profiles compared to the non-metastatic. A prospective validation is needed to evaluate the usefulness of this molecular approach in the early identification of high-risk FVPTCs. Highlights: No molecular signatures are currently available for metastatic potential of FVPTCs. A set of mRNA and miRNA are significantly deregulated in metastatic tumors. A mRNA/miRNA signature could identify FVPTCs at risk to develop metastasis.